Understanding electric vehicle purchase intentions through the technology acceptance model - Utari, Ni Kadek Melia; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2025)
Electric vehicles represent a new technology and an environmentally friendly transportation option for the community. This study analyzes the application of the Technology Acceptance Model (TAM) to understand the purchase intention of electric vehicles among people in Denpasar City. The research involved 200 respondents who had never owned an electric vehicle, selected through purposive sampling. Data were collected via questionnaires and analyzed using SEM-PLS. The study indicates that perceived usefulness and perceived ease of use have a significant and positive impact on users’ attitudes toward using electric vehicles. In addition to this, both perceived usefulness, perceived ease of use, and attitude toward using electric vehicles also directly contribute to purchase intention. Moreover, attitude toward using electric vehicles serves as a partial mediator in the relationship between perceived usefulness, perceived ease of use, and purchase intention. Based on these findings, companies should highlight product advantages such as responsive acceleration, comfortable driving, extended travel range, and smart features. Expanding dealer and authorized workshop networks and increasing public awareness about the environmental benefits of electric vehicles are also important. Governments are encouraged to increase public charging infrastructure, implement carbon emission-based tax policies, and provide incentives for electric vehicle users.